Validation of the instrument “Computer Vision Syndrome Questionnaire (CVS-Q)” for the evaluation of the Computer Vision Syndrome in health personnel of Lima - Aguilar-Ramírez, María Del Pilar (2022)
Objectives: To determine the validity and reliability of the instrument "Computer Vision Syndrome Questionnaire (CVS-Q)" in the measurement of the Computer Visual Syndrome in health personnel in Lima. Methods: A quantitative, observational, descriptive, cross-sectional and questionnaire study was carried out in 82 health workers. Content validity was evaluated by expert judgment with the Aiken V statistical method; construct validity, through factor analysis; discriminant validity, through the receiver operating characteristic curve (ROC) curve contrasted with the CSSV17 questionnaire; internal consistency reliability, with Cronbach's alpha; reliability test - re-test (7 days apart); with Spearman's Rho and Interclass Correlation Coefficient (ICC) with 95% CI. The SPSS software version 20.0 for Windows with a trial license was used for its processing. Results: The V of Aiken obtained a value of 100%. The factor analysis extracted 3 main components that explain 69.455% of the total variance. The area under the ROC curve was 0.889 [(0.845-0,934); CI=0.95] (p=0.000), sensitivity 72.2% and specificity 100%. Cronbach's alpha was 0.939, Spearman's Rho 0.884 (p=0.000) and ICC 0.856 [(0.777 – 0.907); CI=0.95] (p=0.000). Conclusions: The CVS-Q questionnaire is valid and reliable to be applied in the health professionals’ occupational group with good psychometric properties.